2022
DOI: 10.1097/jxx.0000000000000763
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, illness perception, depression, and self-management among African Americans with type 2 diabetes

Abstract: Background: Type 2 diabetes mellitus (T2DM) causes significant morbidity and mortality. Compared with non-Hispanic Whites, African Americans are more likely to suffer and die from T2DM.Purpose: This study examines the associations between health literacy, illness perception, depression, working memory, executive function, and self-management among African Americans (18-65 years) with T2DM.Methodology: A descriptive cross-sectional design was used. Data were collected through Research Electronic Data Capture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The belief that diabetes is communicable was particularly prevalent and concerning, leading to experiences of social isolation and discrimination. Researchers in the United States and Ghana have established that lower health literacy coupled with illness perception is associated with lower self-management behaviors in adults living with T2D [2830]. Medication perception also played a significant role in participants’ experience with T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The belief that diabetes is communicable was particularly prevalent and concerning, leading to experiences of social isolation and discrimination. Researchers in the United States and Ghana have established that lower health literacy coupled with illness perception is associated with lower self-management behaviors in adults living with T2D [2830]. Medication perception also played a significant role in participants’ experience with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…States and Ghana have established that lower health literacy coupled with illness perception is associated with lower self-management behaviors in adults living with T2D [28][29][30]. Medication perception also played a significant role in participants' experience with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…While the study showed that Black/African Americans were less likely to experience mental health issues, we think this is due to the stigma associated with mental illness, thus, underreporting of experiences of such events. It is crucial to note that mental illness, such as depression, usually goes undiagnosed and untreated in the Black/African American population with chronic diseases such as type 2 diabetes (Ajuwon & Insel, 2022). Further research is needed to examine the role of stigma in mental health disparities among Black/African Americans to develop strategies to address this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of illness are mainly concerned with the anxiety and depression levels normally resulting from patients who are suffering from a chronic illness such as DM. Patients with DM usually develop depression and stress, which creates their perception of the disease and certain beliefs about the cause and controllability of the disease [ 9 ]. These perceptions normally affect patients’ medication adherence because patients may perceive the cause of the disease, such as DM, as different from what the doctor prescribed.…”
Section: Introductionmentioning
confidence: 99%